Review of the Pareques acuminatus (Bloch & Schneider, 1801) species complex, with revalidation of Pareques lineatus (Cuvier, 1830) from the Western Atlantic (Percomorphacea: Sciaenidae) - Carvalho-Filho, Alfredo; Oliveira, Claudio [UNESP]; Maximiano, Loriane [UNESP]; Tavera, Jose; Acero, Arturo P.; Marceniuk, Alexandre Pires (Magnolia Press, 2022)
Recently, different studies have revealed the existence of complexes of marine fish species of several genera from the Western Atlantic (e.g., Bagre, Peprilus, Bairdiella, Pogonias and Menticirrhus), with a correspondence between recognized species and well-established geographic areas such as the Gulf of Mexico, the Caribbean, and Brazil, showing the need to improve the taxonomic knowledge of coastal fishes in the region. In this work, we revalidate and redescribe Pareques lineatus (Cuvier, 1830) described from Brazil, and redescribe and designate a neotype to P. acuminatus (Bloch & Schneider, 1801) to differentiate it properly from its congeners. The recognition of P. acuminatus for the east coast of the USA plus the Gulf of Mexico and of P. lineatus for Brazil, with the West Indies and southern Caribbean as an area of overlap, brings new information about biodiversity in Western Atlantic coastal areas and confirms a previously proposed major biogeographical boundary.
Keywords: biogeography; Brazil; molecular phylogeny; taxonomy; types